An Exercise in Liberal Biblical Theology (Keynote Address) - Hill, Robert Allan (Journal of the Council for Research on Religion)

(untitled) (Council for Research on Religion, 2023)
This essay was presented at the “Who is my Neighbour? Theological Education in the Global Villiage of the 21st Century” symposium hosted by the McGill School of Religious Studies in the Fall of 2022. It offers an accessible set of reflections on how a liberal biblical theology can help people connect with the content of the Bible in ways that speak to their lived experience, thereby allowing the heart of the Bible to become more familiar and more widely accessible. In modern society, where the letters G-O-D seem like antiquated fiction and where the church has often failed to adequately and meaningfully explicate the Bible in ways that people can connect with, such a sound, gracious liberal biblical theology can be a source of renewal for both Liberal Protestantism and Christian theological education. To demonstrate this I will undertake an exercise in liberal biblical theology, contrasting the traditional Trinitarian language used by G. B. Caird (1951) to explore the unity of the New Testament with more accessible theological language, language arrived at by drawing from the work of Ralph Harper, Samuel Terrien, Dietrich Bonhoeffer, Eric Fromm, Howard Thurman, and Robert Frost.